The role of mobile network operators in next-generation public safety services - Tapio Savunen; Heikki Hämmäinen; Kalevi Kilkki; Pekka Kekolahti (International Telecommunications Society (ITS), 2022)
Field of research - This research is in the field of public safety communications in mobile broadband 4G/5G networks. The focus is on mobile network operators and their business opportunities in the public safety market. Purpose - The purpose of this research is to provide a review of ongoing public safety mobile broadband projects in which mobile operators play a key role. In addition, a business model analysis is presented to determine the role of mobile operators in these projects. A comparison of the two key business models is also included to reveal their general characteristics. Methods and data - The research used a qualitative method, an inductive case study. This method was used to draw general conclusions from a small number of case studies based on ongoing public safety mobile broadband projects. The Casadesus- Masanell and Ricart framework and the business model canvas were used to analyse and compare the two key business models discussed. Data were collected from a variety of sources, including company reports, press releases, international events and conferences, and selected interviews with managers in charge. Findings - The results show that mobile operators have new business opportunities in the public safety market. Their existing mobile networks can be used for public safety services with certain enhancements. Within existing projects, mobile operators have different business models. The two analysed models are network sharing and the one-stop shop model. These models require different resources and offer different business opportunities for mobile operators. Procurement authorities responsible for selecting business models are encouraged to pay attention to the choice of model based on, for example, strategic objectives. Value - Very little research has been done on the business opportunities of mobile operators in the public safety market. This research brings new knowledge to the area and enables further research. Procurement authorities can use the results when deciding on the business model. Mobile operators can benefit from these results by better understanding their own roles in public safety projects and when assessing the business opportunities of a particular project.
Keywords: 330; mobile network operator; public safety; business model; 4G/5G; mobile broadband